2015
DOI: 10.1007/s10995-015-1686-1
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Education and Immunization Status Among Children in Kenya

Abstract: Child morbidity and mortality due to infectious diseases continues to be a major threat and public health concern worldwide. Although global vaccination coverage reached 90 % for diphtheria, tetanus and pertussis (DTP3) across 129 countries, Kenya and other sub-Saharan countries continue to experience under-vaccination. The purpose of this study was to examine the association between maternal education and child immunization (12-23 months) in Kenya. This study used retrospective cross-sectional data from the 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 33 publications
4
20
0
1
Order By: Relevance
“…Mother's education have been frequently considered as a determinant of child health indicators in many countries. [15][16][17][18][19][20][21] These studies indicated that the educated mothers could be able to enhance the childhood survival through their level of education, which is not surprising in the context of Zhejiang province. In fact, we had found a strong link between mother's education and the UTDFI coverage.…”
Section: Discussionmentioning
confidence: 78%
“…Mother's education have been frequently considered as a determinant of child health indicators in many countries. [15][16][17][18][19][20][21] These studies indicated that the educated mothers could be able to enhance the childhood survival through their level of education, which is not surprising in the context of Zhejiang province. In fact, we had found a strong link between mother's education and the UTDFI coverage.…”
Section: Discussionmentioning
confidence: 78%
“…The positive impact of a higher educational level of parents on children's vaccination status has been confirmed also by other studies. [27][28][29] This survey has several limitations due to the study design. The first is that, since this is a cross-sectional study, it is not possible to establish the causal and temporal direction of association between the outcomes of interest and the predictors.…”
Section: Discussionmentioning
confidence: 99%
“…Kitui County has a poor road network with only 0.3% of roads paved [ 46 ], and is reflective of many other areas in Kenya. This creates challenges in accessing populations and transporting vaccines and health personnel in rural areas [ 60 ]. Pupil absenteeism on the vaccination days is also noted as a major barrier in a study in Tanzania [ 16 ].…”
Section: Discussionmentioning
confidence: 99%